A trial on higher order mutual correlation for acoustic and electromagnetic environment around VDT - Ohta, M.; Fujita, Y. (Archives of Acoustics, 2001)
Nowadays, owing to the rapid and wide application of many type information technology equipments, we are always exposed to acoustic and electromagnetic waves. For evaluating step by step these complicated accumulative and multiplicative effects, it is first important to extract the correlation information among them as deeply and quantatively as possible. In this paper, some new trial of hierarchically evaluating mutual correlation between them is proposed based on the conditional probability density function form derived from a statistical type Hermite series expansion expression for the two-variate joint probability density function. The proposed method has been experimentally confirmed by applying it to the actual environment around VDT.